Do women leaders promote positive change? Analyzing the effect of gender on business practices and diversity initiatives. Issue 4 (19th September 2017) - Glass, Christy; Cook, Alison
Abstract : While most scholarship on gender leadership diversity and organizational outcomes considers the impact of board composition on firm performance, we consider the impact of women CEOs and board members together on a range of organizational outcomes. We test three competing theoretical perspectives related to gender in organizations: gender difference, homophily, and diversity . We rely on a unique data set of CEO characteristics, board composition and firm outcomes of all Fortune 500 companies from 2001 to 2010. We find that firms with women CEOs or gender diverse boards are associated with stronger business and equity practices. We also find that gender diverse leadership teams demonstrate stronger business and equity outcomes than teams characterized by gender homophily.